Changes in habitat use and diet of European bison Bison bonasus, aurochs Bos primigenius and moose Alces alces in Europe in the Holocene - Hofman-Kamińska, Emilia (2021)
Kowalczyk, Rafał Borkowski, Jakub Nadachowski, Adam